ANALISIS PENGARUH CORPORATE GOVERNANCE, PERTUMBUHAN PERUSAHAAN, DAN KEKUATAN PASAR TERHADAP KEBIJAKAN DIVIDEN DI INDONESIA - Resty Ramandini; Etna Nur Afri Yuyetta (Diponegoro Journal of Accounting, 2019)
This study aims to examine the effect of the impact of corporate governance, firms growth, and market power on dividend policy in Indonesia. Independent variabels used in this research is corporate governance, firms growth, and market power while the dependent variabel in this research is the dividend policy.The population of this research is manufacturing companies listed in Indonesia Stock Exchange are always distributed dividends in 2015-2017. This study using purposive sampling method, the total sample obtained amounted to 102. The research data is secondary data from the financial statements and annual reports of companies manufacturing. The analytical method used in this research is multiple regression analysis.The analysis showed that corporate governance does not have a significant effect on dividend policy, firms growth has a significant negative effect on dividend policy, as well as market power have a significant impact to the company's dividend policy.